Elaboração e validação de tecnologia educativa sobre acidente vascular cerebral para prevenção da recorrência - Maniva, Samia Jardelle Costa de Freitas (2016)
Prevention of stroke recurrence is a key measure to reduce new episodes in individuals already affected by the disease. It is believed that the construction and validation of a stroke-type educational technology on stroke is of great relevance. The objective of the study was to elaborate and validate an educational technology of the booklet type on stroke for prevention of recurrence. The study was carried out in two stages. In the first stage, the preparation and validation of content of the booklet took place. In the preparation of the booklet, the subjects were selected through an integrative review and evaluated by eleven specialists. Then, the validation of the appearance of the booklet was performed with ten patients hospitalized with stroke. For the analysis of the data, the Content Validity Index (CVI) was used. In the second stage, a quasi-experimental, before-and-after study was conducted. The validated primer was applied to a group of 87 stroke patients. This stage was developed at the Stroke Unit of the General Hospital of Fortaleza (Ceará) from February to April 2016. The CAP survey was developed by the researcher and previously validated to evaluate patients' knowledge, attitude and practice (Pre-test), immediately after (immediate post-test) and after four weeks (late post-test), via telephone contact. Data were presented through tables and graphs, and discussed based on relevant literature. The mean, median and standard deviation of the following variables were calculated: age, number of years of study, income, symptom onset time and comparison of CAP scores in the three moments. All the ethical aspects were respected, according to Resolution 466/12 of the National Health Council. The educational booklet entitled "Stroke booklet: what it is, what to do and how to prevent" was constituted by seven domains: definition of the disease , Signs and symptoms, emergency action, treatment, risk factors, recurrence of stroke and preventive measures. In the validation of content, the mean of the IVC for each of the evaluative aspects of the booklet was higher than 0.85 and the overall mean of the IVC was 0.94, indicating an excellent degree of agreement among the specialists. Regarding the application of the primer in the patient group, the mean age of the patients was 51.6 years (± 16.1), ranging from 19 to 81 years. The majority were women (51.7%), were married (74.7%) and were employed (67.8%), with a median income of one minimum wage. Regarding the type of stroke, 94% had ischemic stroke. The main risk factors for stroke were sedentary lifestyle (86%), hypertension (66.3%) and diabetes mellitus (24.4%). Previous stroke occurred in 17.3% of patients. Regarding the comparison of means of CAP scores, in the pre-test, knowledge was 3.31 (CI = 3.02-3.61); Attitude 0.63 (CI = 0.43-0.83) and practice 5.12 (CI = 4.61-5.62). In the immediate post-test, knowledge was 5.95 (CI = 5.74-6.16), attitude 1.98 (CI = 1.93-2.02) and practice 11.64 (CI = 11.49- 11.79). In the late post-test, knowledge was 5.25 (CI = 5.02-5.49), attitude 2.00 (CI = 2.00-2.00) and practice 9.91 (CI = 9.59- 10,23). In view of such findings, it can be affirmed that the educational booklet promoted adequate knowledge, attitude and practice in stroke patients, with a view to preventing recurrence.